Repression of Kisspeptin1 weakens hydrogen peroxide‐caused injury in HTR8 cells via adjusting PI3K/AKT/mTOR pathway. Issue 5 (11th February 2020) - Han, Qingfang; Zhang, Wenke; Lu, Caixia; Wu, Jixia; An, Shujing; Zhang, Shiqian
Abstract: Kisspeptin1 (KISS1) is a tumor metastatic suppressor, and its increased expression is validated in human placenta trophoblast cells. Nonetheless, the actions of KISS1 in hydrogen peroxide (H2 O2 )‐impaired human trophoblast HTR8 cells still remain imprecise. This research aims to uncover whether KISS1 can mitigate H2 O2 ‐triggered cell injury. HTR8 cells were pretreated with 250 μM H2 O2 for 4 hours; the autophagic markers (Beclin‐1 and LC3B), cell viability, invasion and apoptosis were appraised. Real‐time quantitative polymerase chain reaction and Western blot trials were enforced for the valuation of KISS1 mRNA and protein levels. After si‐KISS1 transfection and 3‐MA manipulation, the aforesaid biological processes were reassessed for ascertaining the influences of repressed KISS1 in H2 O2 ‐impaired HTR8 cells. Phosphoinositide 3‐kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) pathway was eventually estimated. H2 O2 enhanced Beclin‐1 and LC3B expression, restricted cell viability, and invasion, and meanwhile caused apoptosis. The elevation of KISS1 evoked by H2 O2 was observed in HTR8 cells. In addition, silencing KISS1 was distinctly annulled the function of H2 O2 in HTR8 cells. Eventually, we observed that the repression of KISS1 triggered the activation of PI3K/AKT/mTOR in HTR8 cells under H2 O2 management. The diverting research unveiled that KISS1 repression eased H2 O2 ‐caused HTR8 cells injury via mediating PI3K/AKT/mTOR pathway.